Skip to main content

Questions tagged [conjunctive-normal-form]

A formula is in conjunctive normal form (CNF) if it is a conjunction of clauses, where a clause is a disjunction of literals.

0 votes
1 answer
39 views

Applying Distributivity law on 2 conjunctive statements seperated by a disjunction

I have been given this statement to convert to CNF: $$((a \to x) \land (b \to c)) \to (a \to ¬c)$$ and so far I have gotten rid of the implications and applied de Morgan's law after which I have: ...
Thomas's user avatar
  • 1
0 votes
1 answer
247 views

Is there any procedure that guaranteed to find the Minimal CNF form of an expression $?$

For example: Find the Minimal CNF form of $abcd+a'b'c'd'$: My attempts: Consider $$abcd+a'b'c'd'$$ By Distributeive law we have: $$\boxed{\begin{array}{ccccc}d' &\color{orange}{a+d'}&b+d'&...
Ethan's user avatar
  • 5,283
3 votes
2 answers
1k views

First Order Logic - exactly one predicate is true

I am working on a question for an assignment and I am to declare a clause in Conjunctive Normal Form that says exactly one of three predicates is true. Or given a bit of context - given three suspects ...
Mason Baran's user avatar
0 votes
1 answer
1k views

Convert to Conjunctive Normal Form exercise

I got confused in some exercises I need to convert the following to CNF step by step(I need to prove it with logical equivalence) $1.¬(((a→b)→a)→a)$ $2.¬((p→(q→r)))→((p→q)→(p→r))$
HellfireWorld's user avatar
-1 votes
1 answer
57 views

Combination of AND OR in Linear Programming

I have three binary variables: $x,y,z$. I want to define $U$ as follows: $$U = x \wedge (y \vee z)$$ Following this, I have already tried defining $$yz = y \vee z$$ and then, doing $$U = x \...
Haleh's user avatar
  • 3
2 votes
1 answer
220 views

Logic - Rearranging CNF formula

Given a #2SAT problem such as how many ways can $(a \vee b) \wedge (\bar{a} \vee d) \wedge (\bar{b} \vee c) \wedge (\bar{c} \vee d)$ be satisfied? I am trying to find a way to rearrange the clauses ...
Ben Crossley's user avatar
  • 2,554
1 vote
0 answers
70 views

A fomular for CNF-DNF conversion

I just see this nice generalisation of sets: $$\bigcup_{(i,j) \in I \times J} (A_i \times B_j) = \bigcup_{i \in I} \bigcup_{j \in J} (A_i \times B_j) = \Biggl(\bigcup_{i \in I} A_i\Biggr) \times \...
Ethan's user avatar
  • 5,283
0 votes
1 answer
63 views

Converting Natural Language Problem to CNF

I'm struggling in converting this problem to Conjunctive Normal Form. I'd appreciate any help or guiding. There are $n$ stones in the river. Every stones has two states: above or below the water. ...
One Piece's user avatar
0 votes
1 answer
163 views

conjunctive normal form distribution over logical or?

when converting to CNF do you have to distribute ors over ors ex. (A or B) or C, or can you leave it just like that I am wondering because I have to convert a bunch of first order logic to clausal ...
JRowan's user avatar
  • 381
1 vote
1 answer
92 views

How to show this predicate logic equivalence?

I have been working on an assignment exercise that asks for the conjunctive normal form (CNF) of the logic predicate $\neg (p \iff \neg q \implies r)$. So far I've managed to obtain the expression $(p ...
nsa's user avatar
  • 167
1 vote
0 answers
1k views

A reduction of 3-CNF down to 2-CNF for boolean satisfiability

Could you please review the following candidate solution for the boolean satisfiability problem? It is known that 2-CNF has a polynomial solution. Now consider we have a 3-CNF (AFAIK, it's proven ...
Serge Rogatch's user avatar
0 votes
0 answers
26 views

Convert into CNF form

How could I convert this into CNF? I'm stuck because I don't see anyway to add ANDs in here to get it in the proper from. Usually, I would use DeMorgan's or distribute, but that isn't an option here. ...
fxcd's user avatar
  • 199
1 vote
1 answer
150 views

Boolean algebra - Converting DNF form to CNF form

I´ve tried at least dozen ways to convert DNF to CNF, yet I always end up with something wrong. Here is the DNF: (B ∧ D) ∨ (C ∧ D) ∨ (¬D ∧ ¬B) ∨ (¬D ∧ ¬C) . Is there someone who can help me with it ...
AlZiSVK's user avatar
  • 21
2 votes
1 answer
610 views

Boolean algebra - Converting DNF form to CNF

I've tried at least a dozen ways to convert this DNF to CNF, yet I always end up with something unusable. Here is the DNF: $$y= (A \wedge B \wedge \neg C \wedge D) \vee (A \wedge B \wedge C \wedge \...
Andrej Šereš's user avatar
1 vote
1 answer
78 views

help prove this propositional logic equivalency [duplicate]

I'm really stuck on proving this propositional logic equivalency. I've tried De Morgan's law, and double negation to see if I could get it, but no luck. Any help is greatly appreciated! P.S Please, ...
Fritz Ringler's user avatar

15 30 50 per page
1
5 6
7
8 9
14